4000 Jaar van soeke na God - Klopper, Frances (HTS teologiese studies, 2005)
The 4000-year quest for GodSouth Africans live in a time of growing unease amongst Afrikaansspeaking Christians about the traditional God-image of their childhood. As a con-sequence, churches are losing members – which is of concern to the church’s leaders. By referring to Karen Armstrong’s book, A History of God (1999), this article shows that rethinking the idea of God is not new and that healthy iconoclasm is part and parcel of religions as evolving and changing organisms. Over the past 4000 years, each generation created an image of God that worked for them. The article reflects on the God of Judaism, the Christian God, the God of Islam, the God of the philosophers, the mystics, the reformers and the thinkers of the Enlightenment to the eventual eclipse of God in twentieth-century Europe. The purpose of the exercise is to encourage Christians to engage with the process and create a sense of God for themselves by taking heed of the negative and positive moments in God’s long history.